Prognostic role of FUT8 expression in relation to p53 status in stage II and III colorectal cancer. - Masaru Noda; Hirokazu Okayama; Yasuhide Kofunato; Shun Chida; Katsuharu Saito; Takeshi Tada; Mai Ashizawa; Takahiro Nakajima; Keita Aoto; Tomohiro Kikuchi; Wataru Sakamoto; Hisahito Endo; et al. (PLoS ONE)
The expression of fucosyltransferase 8, an enzyme responsible for core fucosylation encoded by FUT8, influences tumor biology and correlates with patient prognosis in several solid cancers. We hypothesized that p53 alteration modifies prognostic associations of FUT8 expression in colorectal cancer (CRC), since FUT8 has recently been identified as a direct transcriptional target of wild-type p53. Utilizing multiple datasets of microarray and RNA sequence of CRC, FUT8 mRNA was found to be highly expressed in wild-type p53 tumors (n = 382) compared to those of mutant p53 (n = 437). Prognostic values of FUT8 expression in conjunction with the p53 status for disease-free survival (DFS) were analyzed using two independent cohorts of stage II and III CRC after curative surgery, including the immunohistochemistry (IHC) cohort (n = 123) and the microarray cohort (n = 357). In both cohorts, neither FUT8 expression nor the p53 status was associated with DFS. Strikingly, positive expression of FUT8 protein was significantly associated with better DFS only in tumors with negative p53, while it had no prognostic impact in tumors with positive p53 in the IHC cohort. Although not statistically significant, a similar prognostic trend was observed in the microarray cohort when patients were stratified by the p53 status. Our results suggest that the prognostic values of FUT8 expression on DFS may be modified by the p53 status, and the expression of FUT8 protein can be a prognostic biomarker for patients with stage II and III CRC.